Answer:x = 12
Explanation:
The equation One-half x + 3 = two-thirds x + 1 is expressed as
x/2 + 3 = 2x/3 + 1
The first step would be to to find the lowest common multiple of the left hand side of the equation and the right hand side of the equation and multiply the left hand side of the equation and the right hand side of the equation by the lowest common multiple. The lowest common multiple is 6. Therefore,
x/2 × 6 + 3 × 6 = 2x/3 × 6 + 1 × 6
3x + 18 = 4x + 6
4x + 6 = 3x + 18
Subtracting 3x and 6 from the left hand side of the equation and the right hand side of the equation, it becomes
4x - 3x + 6 - 6 = 3x - 3x + 18 - 6
x = 12